The Relation of Personality Traits Wth Depression Severity in Active and Non-Active Elderly Women in Tehran City - Mohammad Ali Aslankhani; Ahmad Farokhi; Parvane Shamsipour Dehkordi; Amir Shams; Mohammad Reza Ghasemian Moghaddam (University of Social Welfare & Rehabilitation Sciences, 2010)
Objectives: The purpose of this study was to investigate the relation of personality traits with depression in active and non – active elderly women in Tehran city. Methods & Materials: The present research is descriptive–correlation. For this purpose, 188 elderly women (94 active and 94 non - active elders) in the age range of 63-82 in Tehran city availably selected as statistical sample. Measurement instrument were demographic questionnaire, Beck depression questionnaire and NEO personality traits questionnaire. Data were analyzed using descriptive statistic (mean and standard deviation) and inferential statistic (independent t test, Pearson correlation and Enter multi variant Regression). Results: Results showed that there was significant difference in personality traits and depression between active women with non-active women elders (P<0.05). Also, the result showed that significant correlation between depression score on neuroticism, extroversion, openness and conscientiousness in active women elders and conscientiousness and openness in non-active women elders (P<0.05). The results of multi variant regression also indicated that openness and extroversion variants in active elders and conscientiousness variant in non-active elders have linear relationship with criteria variant (depression) and can predict its changes. Conclusion: Based on results of present research, sport and physical activity can be afforded the increase of positive personality traits (for example extroversion and openness) and decrease of depression in women elders.